Anisotropic Crouzeix-Raviart Type Nonconforming Finite Element Methods to Variational Inequality Problem with Displacement Obstacle (Journal of Computational Mathematics, 2018)
In this paper, anisotropic Crouzeix-Raviart type nonconforming finite element methods are considered for solving the second order variational inequality with displacement obstacle. The convergence analysis is presented and the optimal order error estimates are obtained under the hypothesis of the finite length of the free boundary. Numerical results are provided to illustrate the correctness of theoretical analysis.